‘This is the country of premature old men’ Ageing and Aged Miners in the South Wales Coalfield, c.1880–1947 - Curtis, Ben (Routledge, 2015)

(untitled) (Cult Soc Hist)
This article considers the effects of work in the south Wales coal industry either side of the turn of the twentieth century and, specifically, the ways in which work aged workers prematurely. It examines the consequences of working practices for miners’ bodies, the expedients utilized by miners to try and cope with the effects of premature ageing, and the consequences for their living standards, experiences and status. It situates these phenomena in the contexts of industrial relations and welfare provision. In so doing, the article engages with historiographies of the life-cycle, the aged, and pensions provision in modern Britain.